PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN NET PROFIT MARGIN TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN DASAR DAN KIMIA YANG TERDAFTAR DI BEI PERIODE 2015-2019 - Lia Andriani Pasaribu; Ester Paulina Siahaan; Putri Angela Sitanggang; Fuji Astuty (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The purpose of this study is to investigate and analyze the influence of current ratio, debt ratio and net asset ratio on the dividend payout ratio of enterprises of all industries and business sectors. business. Basic. 2019. The research method used in this study is the quantitative method. The population of this survey is 72 out of all industrial companies listed on the Stock Exchange of Indonesia (BEI). Thirteen companies were selected using objective mining from this pool. The analytical method used in this study is multiple regression analysis. In this study, it was found that the current ratio has no great influence on the dividend ratio, but the debt ratio has a large negative effect. It has a great impact on the dividend payout ratio of the listed chemical industry and the core industry. From 2015 to 2019 on the Indonesian Stock Exchange. According to the results of the competition, the current ratio, debt ratio and net profit margin have a significant impact on the dividend payment rates of major chemical and industrial companies listed on the stock exchange.